2018
DOI: 10.1002/adsc.201800778
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis of meta‐Arylated Phenol Derivatives by Rhodium(I)‐Catalyzed Arylation of Quinone Monoacetal

Abstract: The first selective synthesis of metaarylphenol derivatives by arylation of quinone monoacetal is reported. The transformation was achieved under Rh(I) catalysis via a formal arylation/demethoxylation process, and valuable metaarylphenols were obtained in high yields under mild conditions. Remarkably, an unprecedented convergent reaction pathway was assumed to be involved.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 9 publications
(2 citation statements)
references
References 70 publications
(12 reference statements)
0
2
0
Order By: Relevance
“…This method was also found very suitable for getting meta-diarylated phenol 125 (Scheme 14). [54] A three-component reaction of para-quinone monoketal 126, α-amino acid 127, and diaryl phosphine oxide was reported by a group of Shen, which introduced 3-(diarylphosphinyl)anilide 128 and N-aryl-2-diarylphosphinylpyrrolidine 129 to the aromatic system very selectively. It was proposed that this transformation may involve the in situ generations of 2-azaallyl anion or conjugated azomethine ylides through decarboxylation from the reaction between compound 126 and α-amino acid which were then trapped by diaryl phosphine oxide (Scheme 15).…”
Section: Reactions Of Para-quinols and 25-cyclo-hexa-dienone Monoketalmentioning
confidence: 99%
“…This method was also found very suitable for getting meta-diarylated phenol 125 (Scheme 14). [54] A three-component reaction of para-quinone monoketal 126, α-amino acid 127, and diaryl phosphine oxide was reported by a group of Shen, which introduced 3-(diarylphosphinyl)anilide 128 and N-aryl-2-diarylphosphinylpyrrolidine 129 to the aromatic system very selectively. It was proposed that this transformation may involve the in situ generations of 2-azaallyl anion or conjugated azomethine ylides through decarboxylation from the reaction between compound 126 and α-amino acid which were then trapped by diaryl phosphine oxide (Scheme 15).…”
Section: Reactions Of Para-quinols and 25-cyclo-hexa-dienone Monoketalmentioning
confidence: 99%
“…In 2003, Smith and coworkers developed a one-pot C–H activation/borylation/oxidation strategy to access meta-substituted phenols with the influence of steric hindrance instead of the electronic effect . Later, Stahl et al elegantly reported the synthesis of meta-substituted phenols via the aerobic oxidative Heck/dehydrogenation of cyclohexenones (Scheme a) . Alternatively, the catalytic dehydrogenation of substituted cyclohexanones has also received considerable attention .…”
mentioning
confidence: 99%